The Use of WhatsApp Messaging by Teachers of Medical Education as a Communication Tool at the Catholic University of Cuenca - Karina Serrano, María Isabel Herrera Jaramillo, Tania Cruz Gavilanes, Yolanda de la N Cruz Gavilanez (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Technological progress in electronic devices and their applications have appeared in various areas, and instant messaging is used in the daily life of each person with a smart phone. This study focused on using WhatsApp by teachers at the Catholic University of Cuenca (UCACUE). The purpose of this study was to understand how much teachers use WhatsApp and, secondly, to find out how useful this tool is for their academic activities. It was a quantitative study that took innovative arguments in everyday life, WhatsApp and its use among higher education teachers. This study conducted a survey with a sample of 63 professors from the Catholic University of Cuenca from the faculties of Medicine, Biopharmacy and Nursing. The results obtained show intensive use of the application. WhatsApp is becoming an effective communication tool between students and teachers because a wide range of people uses it, most of them have smartphones with the WhatsApp application installed, although other options may have an application with better features than WhatsApp. From the research results, it can be concluded that WhatsApp is a widely used tool among teachers and high-level students.